Manajemen Takmir Masjid Dalam Menumbuhkan Kesadaran Diri Sholat Berjamaah Bagi Remaja Masjid Al-Muttaqin di Desa Bentayan Kabupaten Banyuasin - Putri Fersikasari; Kusnadi Kusnadi; Manalullaili Manalullaili (Social Science and Contemporary Issues Journal, 2024)
The thesis with the title "Management of Mosque Takmir in Growing Congregational Prayer Self-awareness for Teenagers of Majid Al-Muttaqin in Bentayan Village, Banyuasin Regency" aims to find out the management of mosque takmir in growing self-awareness of Al-Muttaqin mosque youth in Bentayan Village, Banyuasin Regency. This research uses a qualitative approach that is descriptive in nature which examines and describes the problem clearly. Data collection techniques by way of observation, interviews, and documentation. then the data were analyzed consisting of data reduction, data presentation and drawing conclusions/verification. In this study, there is a background problem, namely the Al-Muttaqin Mosque in Bentayan Village, at first, there was still no self-awareness to pray in congregation, then the mosque's takmir managed it with TOT (Training Of Trainer) programs, but for teenagers in Bentayan Village it is still his awareness has not yet grown to pray in congregation at the Al-Muttaqin Mosque, Bentayan Village, Banyuasin Regency. Based on the results of the discussion in the previous chapters, it can be concluded that the Management of Mosque Takmir in Growing Congregational Prayer Self-awareness for Youth Al-Muttaqin Mosque, Bentayan Village, Banyuasin Regency, namely having Planning (growing youth self-awareness and improving the quality of worshipers with the TOT program). Organizing (conducting outreach with youth and other congregations regarding the importance of these activities). Actuating (Implementation of activities begins with sending training program invitations to 40 mosque administrators and youth to attend the TOT activity event). Controlling (controlling all activities including TOT activities, so that activities can be more effective and get maximum results in growing self-awareness for youth and other worshipers to pray in the mosque and prosper the mosque). Evaluation (TOT activities as a handle on improving the quality of youth in mosques and other mosque congregations, this activity can be effective, if it can be done consistently). The results of the study show that mosque takmir management has an important role in growing mosque youth's self-awareness regarding congregational prayers. This was achieved through several management strategies through training in TOT (Training Of Trainers) activities. The existence of these activities mosque youth get a positive attitude and begin to realize the importance of praying in congregation at the mosque.